Stimulus Timing-Dependent Plasticity in Dorsal Cochlear Nucleus Is Altered in Tinnitus - Koehler, Seth D. (Society for Neuroscience, 2013)
Tinnitus and cochlear damage have been associated with changes in somatosensory-auditory integration and plasticity in the dorsal cochlear nucleus (DCN). Recently, we demonstrated in vivo that DCN bimodal plasticity is stimulus timing-dependent, with Hebbian and anti-Hebbian timing rules that reflect in vitro spike timing-dependent plasticity. In this in vivo study, we assessed the stimulus timing dependence of bimodal plasticity in a tinnitus model. Guinea pigs were exposed to a narrowband noise that produced a temporary elevation of auditory brainstem response thresholds. A total of 60% of the guinea pigs developed tinnitus as indicated by gap-induced prepulse inhibition of the acoustic startle. After noise exposure and tinnitus induction, stimulus timing-dependent plasticity was measured by comparing responses to sound before and after paired somatosensory and auditory stimulation presented with varying intervals and orders. In comparison with Sham and noise-exposed animals that did not develop tinnitus, timing rules in verified tinnitus animals were more likely to be anti-Hebbian and broader for those bimodal intervals in which the neural activity showed enhancement. Furthermore, units from exposed animals with tinnitus were more weakly suppressed than either Sham animals or exposed animals without tinnitus. The broadened timing rules in the enhancement phase in animals with tinnitus, and in the suppressive phase in exposed animals without tinnitus was in contrast to narrow, Hebbian-like timing rules in Sham animals. These findings implicate alterations in DCN bimodal spike timing-dependent plasticity as underlying mechanisms in tinnitus, opening the way for a therapeutic target.